Милован Жиласын коммунист тоталитаризмыг шинжлэн шүүмжилсэн нь - Ж.Жаргал, (Politology, 2023)
Товч хураангуй: Энэхүү өгүүлэл нь Югославын улс төр судлаач, төрийн зүтгэлтэн М.Жиласын "Тоталитаризмын дүр төрх" номонд анализ хийхийг зорьсон болно. Уг бүтээлд Югославын коммунист нам, тоталитар дэглэм дэх социалист төрийн үйл ажиллагааг дэлгэрэнгүй авч үздэг бегеед Жиласын Сталинтай уулзаж байсан дурсамжуудыг тодорхой өгүүлсэн байдаг. ABSTRACT This article analyzes the ideas and conclusions of the book M. Djilas "Face of totalitarianism." In this book, the Yugoslav political scientist and politician M. Djilas reveals the inner expansion of the Communist Party of Yugoslavia, illustrates the development of socialist state in a totalitarian regime. This book shows the political documentary portrait of Stalin. In this paper, these and other ideas of M. Djilas discussed in aspect of the history of political thought.